Nutritional programming of hypothalamic development: critical periods and windows of opportunity - Bouret, S G (Int J Obes Suppl, 2012)
Obesity is increasing at an alarming rate throughout the world, particularly among children. Epidemiological and experimental data have suggested that suboptimal nutrition and growth during prenatal and/or postnatal life can have a significant role in the development of obesity and related diseases. Similarly, exposure to malnutrition during perinatal life can result in lifelong metabolic disorders. Although the precise biological mechanisms governing metabolic programming have not been fully elucidated, there is growing evidence that obesity and other metabolic diseases may result from a change in the underlying developmental program of the hypothalamic pathways that regulate energy balance. The hypothalamus undergoes tremendous growth beginning in the embryonic period and continuing through adolescence, and an alteration in perinatal nutrition can affect various developmental processes, including neurogenesis and axon growth, which can lead to abnormal hypothalamic development. Metabolic hormones, particularly leptin, are capable of transmitting signals to the developing hypothalamus in response to alterations in the nutritional environment and may underlie potential maladaptive responses to early metabolic perturbations. A better understanding of the optimal perinatal hormonal and nutritional environment during hypothalamic development may help ameliorate and reverse the metabolic malprogramming of the fetus and/or neonate.